2008
DOI: 10.1590/s0102-76382008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento cirúrgico da fibrilação atrial crônica com eletrocautério convencional em cirurgia valvar mitral

Abstract: Results: The mean time of extracorporeal circulation was 52.5 ± 13.3 min; aortic clamping, 35.6 ± 12.9 min; atrial ablation, 3.05 ± 0.16 min. All the patients were free of atrial fibrillation after the procedure; on hospital discharge, 69.5%; at 6 months, 91.3%; at 12 months, 76.4%; at 18 months, and at 24 months, 68.4%. At 12 months, left atrium mean diameter was 42.1 ± 3.5 mm; left ventricular ejection fraction was 59.2 ± 3.48%; In addition, left atrial contractility was present in 68.8% of the patients. 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Gomes et al [ 45 ] , using electrocautery in mitral valve surgery, found that this source of energy reversed arrhythmia in a significant number of patients. In the absence of ultrasound equipment, Brick (personal communication) had the opportunity to use electrocautery in a small number of patients, not recommending its routine use due to charring with the release of small emboli inside the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Gomes et al [ 45 ] , using electrocautery in mitral valve surgery, found that this source of energy reversed arrhythmia in a significant number of patients. In the absence of ultrasound equipment, Brick (personal communication) had the opportunity to use electrocautery in a small number of patients, not recommending its routine use due to charring with the release of small emboli inside the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…(86) A fonte de energia ideal seria rápida, confiável, com produção de lesão transmural, que não danificasse os tecidos circundantes, sendo passível de usar com CEC, de aplicação minimamente invasiva, por via endocárdica e epicárdica. (105) Gomes et al, (106) utilizando eletrocautério em cirurgia valvar mitral, verificaram que essa fonte de energia reverteu arritmia em número significativo de pacientes. Brick (comunicação pessoal) teve oportunidade, na ausência do equipamento de US, de utilizar eletrocautério em pequeno número de pacientes, não recomendando seu uso rotineiro por provocar carbonização com liberação de pequenos êmbolos dentro do átrio.…”
Section: Discussionunclassified
“…No mortality occurred in our study as well; however, 14 patients required temporary and six patients required permanent pacemakers. In 2008, Gomes Junior et al [23] published a similar study on 33 patients undergoing ablation with electrocautery for AF during MVS. The authors presented parallel results to ours and reported low mortality and morbidity rates.…”
Section: Discussionmentioning
confidence: 99%